(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The research work was conducted at the Artificial Insemination (AI) Center under the Department of Animal Breeding and Genetics, Bangladesh Agricultural University, Mymensingh to compare the efficacy between Egg Yolk Citrate (EYC) and Tris extenders for cryopreserved semen production in Black Bengal buck. The parameters of semen characteristics included percentage of individual motility (progressive), normal and live sperm and sperm concentration (billion/ml). Statistical analysis of fresh semen of individual buck effect was found to be significant (p<0.01) on normal sperm percentage but insignificant on individual motility, sperm concentration and live sperm percentage. After dilution with EYC extender, individual bucks had significant effect (p<0.05) on sperm motility and but insignificant on motility after cooling with and without glycerol. In the same way with Tris extender, it was insignificant (p>0.05) on diluted semen motility and motility after cooling with and without glycerol. Motility and morphology of the sperm after equilibration and thawing showed insignificant difference among the bucks using EYC extender. On the other hand, variation in the motility after equilibration and thawing was found significant (p<0.05) using Tris extender and insignificant on normal and live sperm percentages. Res. Agric., Livest. Fish.6(1): 119-125, April 2019